CONCEPTS OF CYBERCRIME, CYBERLAW AND CYBERETHICS - Mirzamakhmudov Azamatjon Bakhtiyar o’g’li (Web of Journals Publishing, 2024)
In the thesis, the provision of information security in today's modern computer systems, the identification of weaknesses in the provision of information security in computer networks, their evaluation and analysis are studied and analyzed.
Keywords: cybercrime, internal and external cybercrime, cyberlaw, cyberethics, integrity, privacy, confidentiality.